Apremilast improves endothelial glycocalyx and microvascular perfusion: a possible protective mechanism against COVID-19. (14th October 2021) - Ikonomidis, I; Pavlidis, G; Thymis, J; Rafouli-Stergiou, P; Makavos, G; Kostelli, G; Katsimbri, P; Lambadiari, V; Parissis, J; Kapniari, E; Katogiannis, K; Kountouri, A; et al.
Abstract: Background/Introduction: The phosphodiesterase 4 inhibitor apremilast is an approved treatment option for psoriasis. Purpose: We aimed to investigate the effects of apremilast on endothelial glycocalyx, vascular and left ventricular (LV) myocardial function in psoriasis. Methods: Ninety patients with psoriasis were randomized to receive apremilast (n=30), anti-tumor necrosis factor-a (etanercept, n=30), or cyclosporine treatment (n=30). At baseline and 4 months post-treatment, we measured: (1)Perfused boundary region (PBR) of the sublingual microvessels with a diameter 5–25μm using a dedicated camera (Sidestream Dark Field imaging, Microscan, Glycocheck). Increased PBR indicates reduced glycocalyx thickness. Perfused microvascular density (PMD), an index of microvascular perfusion, was also measured. (2)Pulse wave velocity (PWV - Complior; ALAM Medical) and central systolic blood pressure (cSBP), and (3)LV global longitudinal strain (GLS) and percent difference between peak twisting and untwisting at mitral valve opening (%dpTw-UtwMVO) using speckle-tracking echocardiography. Results: Compared with baseline, PBR20–25 decreased only after apremilast treatment (−13% at 4 months, P<0.05) whereas no statistically significant changes in PBR20–25 were observed after etanercept or cyclosporine. Compared with etanercept and cyclosporine, apremilast resulted in a greater increase of PMD (+12% versus +3% versus +3%) and in a higher reduction of PWV (−10% versus −3% versus +8%) and cSBP (−8% versus −2% versus +7%) at 4 months. Apremilast showed a greater increase of GLS (+12% versus +5% versus +2%) and %dpTw-UtwMVO (+15% versus +3% versus +3%) than etanercept and cyclosporine (P<0.05 for all comparisons). Changes of PBR and PMD post-apremilast treatment correlated with a concomitant reduction of PWV and cSBP (P<0.05). Conclusions: In psoriasis, apremilast confers a greater improvement of endothelial glycocalyx, microvascular perfusion and LV myocardial function compared with etanercept or cyclosporine treatment. Apremilast restores glycocalyx integrity and thus reduces vascular permeability to pro-inflammatory molecules. This may explain the beneficial effects of apremilast on COVID-19. Funding Acknowledgement: Type of funding sources: None.